The Quest for Beauty in Rabindranath Tagore’s Poetry - Mohammad Shafiqul Islam; Rashed Mahmud (Crossings, 2014)
Rabindranath Tagore (1861-1941) pursued beauty all through his life. In his quest for beauty, he passed through many stages of development. His early poems incorporate sensuous observations of nature. The effect of sensuous magnetism persists, but the soul is awakened towards a greater vista of beauty. The soul keeps searching and comes to the conclusion that mere sensuous beauty is not the goal; it needs a revelation of a deeper meaning. He finds beauty in harmony with the inner and the outer principles of nature midway through his poetic life. It is also at this stage that he finds beauty and truth synonymous. To find the absolute beauty, the Infinite, Tagore reaches the final stage where he discerns God and seeks communion with Him. The paper aims at showing how Tagore sees beauty in every object of this universe; how he correlates beauty and truth; and how he seeks communion with the Infinite, the definitive source of all beauty and truth.